Entrepreneurial Innovation Mediation among Marketing Strategies and Business Sustainability in Ethiopia - Wata , Jalata; DejeneYadete , Fisseha; Adula, Metasebia; Jio, Wako; Kant, Shashi (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2023)
Present study was conducted to examine the predicators of marketing strategies on the organizational performance with mediation of entrepreneurship innovation in Sustainable business scenario. The researchers had designed both descriptive and inferential statistics and different methodologies. The sampling technique was both non-probability and probability incorporating simple random sampling technique. The data for this study were obtained from Oromia International Bank, Ethiopia as the representative organization with a survey of 425 customers of Oromia International Bank, those served in sectors and modern organizations staff of Bule-Hora branch, Ethiopia. The researchers, finally come up with the result, of less marketing strategy implementation and the decreasing the organization performance which are mainly associated with poor leaders capacity, Work environment and poor Employees commitment and poor technology adoption ,related predicators were among the major problems while adoption of mediation of entrepreneurship innovation . Leader’s capacity is single of the most promising ways to increase organization performance in Ethiopia. The researchers recommended that the concerned body had to have applied so as to end up with the problems observed in marketing strategy implementation, control the predicators, and in turn provide good marketing strategy implementation as well as good organization performance.